CT in Acute Abdomen: Radiomics for Differentiating Appendicitis, Colitis, and Diverticulitis — A Study of 60 Cases - Dr. Manoj Landge, Dr. Shalik Aade, Dr. Nitin Mahajan, Mr. Vishal Pol (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Acute abdomen is a common emergency presentation. Differentiatingappendicitis, colitis, and diverticulitis solely on clinical features may be challenging.Radiomics extracted from CT imaging offers quantitative features that may enhance diagnostic accuracy.